Bagé : a imprensa partidária e a Guerra Civil de 1923 - Lemieszek, Cláudio de Leão (2010)
This dissertation aims to analyze the journalistic-political speech in the context of the 1923 Civil War, from the coverage done by the newspaper press of the city of Bagé, especially the ones by the newspapers O Dever and Correio do Sul. This study intends to investigate and discuss the role and the relationships of the political party journalistic press in the city during the war, having as a main goal to show that the two newspapers had a role in the conflict, by promoting revolutionary slogans or contributing to the pacification initiatives. The theoretical assumptions which make up the interrelationship game between journalism and the public life were highlighted introductorily, reviewing the political party debate in both newspapers